Soybean yield, nutrient use efficiency, and economic returns of phosphorus and potassium in Ghana’s interior savanna - Awuni, George A.; Dodds, Darrin M.; Reynolds, Daniel B.; Asungre, Peter A.; Yahaya, Iddrisu; Mahama, George Y.; Bella, Thomas; Abongo, Simon; Goldsmith, Peter D. (Frontiers in Agronomy, 2024)
IntroductionPhosphorus (P) and potassium (K) deficiencies are increasingly being reported in Ghana’s interior savanna soils. Smallholder farmers consider soybeans as a “zero-input” crop resulting in low yields and profitability. Studies indicate a positive response to P application; however, knowledge of the synergistic effect of P and K in soybeans is limited. A six-site year experiment was conducted to evaluate the synergy of P and K for soybean yield, partial factor productivity (PFP), agronomic efficiency (AE), rain-use efficiency (RUE), and variable-cost ratio (VCR).Materials and methodsThe treatments were 4 × 4 factorial combinations of P at 0, 25, 50, and 100 P2O5 (kg ha−1) and K at 0, 25, 50, and 100 K2O (kg ha−1), and their combinations laid out in a randomized complete block design with four replications. The soybean cultivar “Favor” (TGx 1844–22E), released and registered by the Savanna Agricultural Research Institute (SARI), was used as the test crop.Results and discussionFlowering time was reduced at Nyankpala and Dokpong by 0.2 and 0.4 (days), while plant height was increased by 4%–18% over control. Yield and RUE increased as P and K rates increased, with the greatest yield from T15 (P100K50) in Manga (2.34 t ha−1) and Nyankpala (2.37 t ha−1), T16 (P100K100) at Dokpong (2.68 t ha−1), and RUE from T15 across locations. The PFP, AE, and VCR values decreased with increasing P and K rates, with the greatest PFP, AE, and VCR from T5 (P25K0) at Manga and Dokpong and T2 (P0K25) at Nyankpala. All treatments exceeded the VCR > 2.0 threshold, except T12 (P50K100) across locations, and T16 at Manga and Nyankpala. The greatest economic returns are T5 at Manga and Dokpong and T2 at Nyankpala.ConclusionBy all indications, the study justified the use of nutrient input in soybeans of P and K to enhance grain yield and profitability. Avoiding broadcast applications and adopting precision placement using the 4R nutrient principles of right placement, right fertilizer source, right rate, and the right time is key. The study recommends further experiments on different combinations of P and K in a long-term residual study.